Gap Junction Remodeling and Spironolactone-Dependent Reverse Remodeling in the Hypertrophied Heart - Qu, Jiaxiang (2008)
Pressure overload is a common pathological insult to the heart and the resulting hypertrophy is an independent risk factor for sudden cardiac death. Gap junction remodeling (GJR) has been described in hypertrophied hearts; however, a detailed understanding of the remodeling process and its effects on impulse propagation is lacking. Moreover, there has been little progress developing therapeutic strategies to diminish GJR. Accordingly, transverse aortic banding (TAC) was performed in mice to determine the effects of progressive pathological hypertrophy on connexin (Cx)43 expression, posttranslational phosphorylation, gap junction assembly, and impulse propagation. Within 2 weeks after TAC, total and phospho-Cx43 abundance was reduced and incorporation of Cx43 into gap junctional plaques was markedly diminished. These molecular changes were associated with progressive slowing of impulse propagation, as determined by optical mapping with voltage-sensitive dyes. Treatment with the aldosterone receptor antagonist spironolactone, which has been shown to diminish sudden arrhythmic death in clinical trials, was examined for its effects on GJR. We found that spironolactone blunted the development of GJR and also potently reversed established GJR, both at the molecular and functional levels, without diminishing the extent of hypertrophy. These data suggest a potential mechanism for some of the salutary electrophysiological and clinical effects of mineralocorticoid antagonists in myopathic hearts.